A scoping review about social and emotional wellbeing programs and services targeting Aboriginal and Torres Strait Islander young people in Australia: understanding the principles guiding promising practice - Himanshu Gupta; Noemi Tari-Keresztes; Donna Stephens; James A. Smith; Emrhan Sultan; Sian Lloyd (BMC, 2020)
Abstract Background Multiple culturally-oriented programs, services, and frameworks have emerged in recent decades to support the social and emotional wellbeing (SEWB) of Aboriginal and Torres Strait Islander (Aboriginal) people in Australia. Although there are some common elements, principles, and methods, few attempts have been made to integrate them into a set of guidelines for policy and practice settings. This review aims to identify key practices adopted by programs and services that align with the principles of the National Strategic Framework for Aboriginal and Torres Strait Islander Peoples' Mental Health and Social and Emotional Wellbeing 2017-2023. Methods A comprehensive review of electronic databases and organisational websites was conducted to retrieve studies of relevance. Twenty-seven publications were included in the review. Next, we identified promising practices through a collaborative review process. We then used the principles articulated in the above-mentioned framework as the basis to complete a framework analysis. This enabled us to explore the alignment between current scholarship about SEWB programs and services with respect to the principles of the framework. Results We found there was a strong alignment, with selected principles being effectively incorporated into most SEWB program and service delivery contexts. However, only one study incorporated all nine principles, using them as conceptual framework. Additionally, 'capacity building', 'individual skill development', and 'development of maladaptive coping mechanisms' were identified as common factors in SEWB program planning and delivery for Aboriginal people. Conclusion We argue the selective application of nationally agreed principles in SEWB programs and services, alongside a paucity of scholarship relating to promising practices in young people-oriented SEWB programs and services, are two areas that need the urgent attention of commissioners and service providers tasked with funding, planning, and implementing SEWB programs and services for Aboriginal people. Embedding robust participatory action research and evaluation approaches into the design of such services and programs will help to build the necessary evidence-base to achieve improved SEWB health outcomes among Aboriginal people, particularly young people with severe and complex mental health needs.